Analysis of the unstable mutation responsible for myotonic dystrophy. - Barcelo, Juana M. (University of Ottawa (Canada), 1997)
Myotonic dystrophy (DM) is an autosomal dominant genetic disease which affects approximately 1 in 8000 individuals globally. This is a multisystemic disorder which primarily targets muscle tissues. The genetic defect underlying DM is a highly unstable trinucleotide CTG repeat sequence located in the 3$\sp\prime$ untranslated region of a gene encoding a protein with serine/threonine protein kinase activity. The number of CTG repeats in non-DM individuals ranges from 5 to 35, whereas in DM individuals it can range from 50 to over 2000. The mechanism of disease and the role of the kinase are currently unknown. The main characteristics of the mutation are its expanded length and high instability. The instability usually leads to an increase in the number of CTG repeats as the mutant allele is transmitted from one generation to the next. This is seen concurrently with an increase in the severity of the clinical phenotypes through successive generations. The mechanism(s) underlying the unstable behaviour of this mutation have been unknown. I studied several possible elements that might affect the observed instability. These studies were performed on a large number of intergenerational transmissions of the mutant allele in DM patients, as well as on different tissues from the same patients. In vivo studies revealed that both the gender of the transmitting parent and the size of the mutation had a significant effect on its intergenerational dynamics. Instability was also seen in cells that underwent mitosis and meiosis, as well as in patients' cells with very low mitotic activity. In addition, in vitro studies showed instability of this sequence in cells from DM patients which were grown in tissue culture. This instability was seen to not necessarily be associated with the cell-cycle-coupled DNA replication in those cells. Since my previous analyses had ruled out recombination between homologous chromosomes as a major element involved in the instability I focused my studies on tests for the possibility that DNA repair was associated with the instability of this mutation. These analyses revealed that there were breaks or gaps occurring specifically within the mutation. Since breaks and gaps are DNA repair intermediates this suggested that the high instability of this mutation in DM patients was due to repair attempts on the structure adopted by the long arrays of CTG repeats. The results of the previous studies on intergenerational transmissions of the mutation, as well as in vivo and in vitro studies of the unstable properties of this sequence are also compatible with a DNA repair model of repeat instability. These data point the way to a more focused approach to the identification of specific mechanistic pathway's underlying the expansion of this highly unstable CTG repeat in DM. The results of this research may also help in defining the mechanism(s) of expansion of the mutations of an increasing number of human genetic diseases found to be caused by highly unstable trinucleotide repeats.
Keywords: Biology, Molecular.